Performance of Earthworms in Cow Dung and Blotong Media and The Quality of Their Vermicompost - Liberty, Sandra; Salundik, Salundik; Endrawati, Yuni Cahya (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
Vermicomposting is a process of consuming organic matter by involving the cooperation of earthworms and microorganisms. The result of this process is vermicompost which is very useful for plants. Earthworm Lumbricus rubellus, Pheretima sp., and Eisenia fetida are three earthworm species that have high potential in the vermicomposting. The research aim was to analyze the productivity of earthworms using cow dung and blotong and the quality of the vermicompost. The experimental design used in earthworm cultivation is a completely randomized design (CRD) of the factorial pattern, while a completely randomized design (CRD) was used for laboratory analysis. The results showed the highest body weight growth in treatment combination of fermented blotong with E. fetida; obtained the most increased cocoon production in treatment combination fermented blotong with L. rubellus. Species treatment E. fetida produces more cocoons than L. rubellus and Pheretima sp. The best vermicompost and the highest growth of kale from fermented blotong feed. Keywords: blotong, cow dung, earthworms, vermicomposting